Spectral analysis of Monte Carlo calculated fluence correction and cema conversion factors for high-energy photon beams at different depths - Roers, Julian; Czarnecki, Damian; Alissa, Mohamad; Zink, Klemens (Frontiers in Physics, 2023)
Purpose: The aim of this study is to investigate the depth-dependent detector response of detailed thimble air-filled ionization chambers by calculating spectral charged particle fluence correction factors at different depths in water. Those spectral correction factors will help to understand, how the detector response varies at different depths and what kind of influences disparate effects have on the spectral detector response. Methods: The cema-approach can be used to obtain spectral charged particle fluence-based correction factors for various measurement conditions by substituting the commonly well-known dose conversion factor with a conversion factor based on the dosimetric quantity cema ("converted-energy per unit mass"). The resulting spectral fluence correction factors were calculated with the EGSnrc software toolkit and analyzed for two air-filled cylindrical ionization chambers (PTW type 31021 Semiflex 3D, SNC125c) at different depths in a water phantom irradiated with a 6 MV linear accelerator x-ray spectrum. The ionization chamber models have been stepwise decomposed to investigate the perturbation caused by internal and external effects on the fluence distribution within the detector. Results: Monte Carlo calculated fluence-based perturbation correction factors revealed that for all investigated detectors, considerable fluence disturbances occur, especially in the build-up region of depth-dose curves. Our results have shown that even slight variations in depth can have major consequences on the differential charged particle fluence within the ionization chamber, mainly due to internal cavity-specific effects. Furthermore, the results showed that in the case of relative dose measurements, the depth-depending detector response can significantly differ from unity in a range of 1.4% to 2.8% depending on the ionization chamber design. Conclusion: The complexity of different effects on the fluence disturbance could be broken down with regard to their influence on the spectral fluence distribution in the sensitive volume of the investigated detectors. It could be demonstrated, that the displacement of water is a depth-depending effect, which can not be compensated or corrected ideally for each investigated water depth by the shift of the effective point of measurement. Generally, the spectral analysis of those energy-dependent correction factors serves to a deeper understanding of the detector response under various conditions.